Overexpression of Heat Shock Protein 70 Ameliorates Meat Quality of Broilers Subjected to Pre-Slaughter Transport at High Ambient Temperatures by Improving Energy Status of Pectoralis Major Muscle and Antioxidant Capacity - Tong Xing; Xinglian Xu; Lin Zhang; Feng Gao (MDPI AG, 2022)
The induction of heat shock protein 70 (HSP70) potentially mediates meat-quality development under stress conditions. To investigate the effects and mechanism of HSP70 on the meat quality of the pectoralis major (PM) muscles of broilers exposed to pre-slaughter transport, a total of 168 broilers were intraperitoneally injected with L-glutamine (Gln) or saline. Twenty-four hours later, broilers were subjected to transport or held under normal living conditions. The results indicated that acute Gln supplementation significantly increased HSP70 expression in the PM of transported broilers (p < 0.05). The overexpression of HSP70 significantly alleviated the decreases in muscle pH and water-holding capacity and improved the shrinking of muscle fibers induced by transport (p < 0.05). HSP70 induction increased ATP content, decreased the activities of glycolytic enzymes, and lowered the phosphorylation level of AMP-activated protein kinase in transported broilers (p < 0.05). In addition, the overexpression of HSP70 greatly increased total superoxide dismutase and the total antioxidant capability and decreased the levels of reactive oxygen species, malonaldehyde, and carbonyls in the PM of transported broilers (p < 0.05). Overall, this work indicated that HSP70 could effectively improve the meat quality of transported broilers by improving the energy status, inhibiting glycolytic influx, and restoring redox homeostasis.